Deciphering the intrinsic dynamics from the beam‐induced atomic motions in oxide glasses. (11th August 2020) - Chushkin, Yuriy
Abstract : Analysis of the X‐ray beam‐induced dynamics in oxide glasses probed by X‐ray photon correlation spectroscopy is presented. The results offer the possibility to estimate true sample relaxation time by performing two measurements with different X‐ray fluxes. Abstract : Probing the microscopic slow structural relaxation in oxide glasses by X‐ray photon correlation spectroscopy (XPCS) revealed faster than expected dynamics induced by the X‐ray illumination. The fast beam‐induced dynamics mask true slow structural relaxation in glasses and challenges application of XPCS to probe the atomic dynamics in oxide glasses. Here an approach that allows estimation of the true relaxation time of the sample in the presence of beam‐induced dynamics is presented. The method requires two measurements either with different X‐ray beam intensities or at different temperatures. Using numerical simulations it is shown that the slowest estimated true relaxation time is limited by the accuracy of the measured relaxation times of the sample. By analyzing the reported microscopic dynamics in SiO2, GeO2 and B2 O3 glasses, it is concluded that the beam‐induced dynamics show rich behavior depending on the sample.